Nilai Sosial Rumah Lontiok di Desa Pulau Belimbing Kabupaten Kampar - Irmasolina Irmasolina; Hasnah Faizah; Elmustian Rahman; Syafrial Syafrial (Journal on Education, 2023)
Indonesia is a country that is rich in language, culture, customs and is also rich in traditional houses or traditional houses. A traditional or traditional house is a building with a structure or shape that has its own characteristics as a characteristic or identity of an area and in general, traditional houses are built using local materials. One of the traditional houses in Riau that still exists and is well maintained is the Lontiok House. The Lontiok house has ornaments and architecture like a stilt house which has stairs, steps and a gate in front which signifies respect for every guest who comes to the Lontiok house and also respects the host himself. The philosophy and value of the gate or pavilion of the lontiok house is to respect one another. This study discusses the social values ​​of Lontiok Houses with the aim of describing the social values ​​contained in Lontiok Houses. The benefits obtained from this research can make a foothold to the general public that the Lontiok house is one of Riau's cultural heritage. The research method used in this research is a qualitative research method with a descriptive approach. Collection of library research data and field research. Library research relies almost entirely on data from libraries. The results obtained in this study are that there are seven social values ​​contained in the Lontiok house, namely: 1) Social kinship values ​​(deliberation), 2) Religious values, 3) Economic values, 4) values ​​of togetherness or affection, 5) Values ​​of please helping, 6) the value of tolerance and 7) the value of caring.